2022
DOI: 10.1093/arclin/acac001
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Performance in Autoimmune Limbic Encephalitis: Evidence from an Immunotherapy-Naïve Cohort

Abstract: Objective Autoimmune limbic encephalitis (ALE) is characterized by memory impairment, psychiatric symptoms, and epileptic seizures. Though, the neuropsychological profile of ALE is not yet well defined. However, there is some evidence that neuropsychological impairments might exceed those related to the limbic system and that different autoantibodies (AABs) are associated with distinguishable pattern of neuropsychological impairments. We provide a comprehensive presentation of neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…No difference in emotional discrimination was found between the two groups. Previous studies have reported impaired emotion processing at acute phases of the disease, 38 , 39 and the evidence points to recovery after treatment. However, impaired emotion recognition 40 and abnormalities in emotional regulatory processes 41 have been reported in chronic ALE as well.…”
Section: Discussionmentioning
confidence: 89%
“…No difference in emotional discrimination was found between the two groups. Previous studies have reported impaired emotion processing at acute phases of the disease, 38 , 39 and the evidence points to recovery after treatment. However, impaired emotion recognition 40 and abnormalities in emotional regulatory processes 41 have been reported in chronic ALE as well.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported variable memory outcomes across different ab-mediated AE subtypes, with reports of both normal and abnormal memory function [2][3][4][5][6][7]. The heterogeneous findings might be due to the different approaches used to detect memory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…This emphasises the importance of comprehensive assessment approaches in understanding memory deficits, particularly in the context of neuroimmunology populations like AE, where memory deficits may coexist with impairments in attention and executive functions, contributing to functional memory difficulties. This is particularly important as there is evidence of a number of cognitive deficits in AE patients [4,5,7,9,10]. Collectively, these factors limit the ability to draw clear conclusions regarding memory impairments after AE.…”
Section: Introductionmentioning
confidence: 99%
“…letter) and semantic (e.g. animals) lexical retrieval, as well as visual confrontation naming, yielded results that, on average, fell within age-expected ranges, where impairment was defined at one standard deviation below expectations [ 4 ]. However, frequency analysis indicated impairments in 23.5% of the cohort on a naming test, 25.0% on lexical word fluency, and 33.3% on semantic word fluency [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…animals) lexical retrieval, as well as visual confrontation naming, yielded results that, on average, fell within age-expected ranges, where impairment was defined at one standard deviation below expectations [ 4 ]. However, frequency analysis indicated impairments in 23.5% of the cohort on a naming test, 25.0% on lexical word fluency, and 33.3% on semantic word fluency [ 4 ]. A systematic review of anti-NMDAR ab-mediated AE patients in the chronic stage of disease (greater than 12 months after initial administration of immunotherapy) reported language impairments in 28.6% of cases, highlighting that there can be potential persistence of deficits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%